ANALYSIS OF REPORTING AND FINANCIAL ACCOUNTABILITY IN DAWUAN KALER VILLAGE SUBANG REGENCY FOR 2022 FISCAL YEAR - Syifa Salsabila Muslim; Syifa Naylla Az-Zahra; Nanda Ayu Triani; Tri Sandi Eka (STIESA Press, 2023)
Village financial management is the whole of activities that include aspects of planning, implementing, administering, reporting and accountability of village finances. Village financial management is considered good based on the ability of its human resources to manage and in accordance with existing regulations. Village Financial Management is regulated in the Regulation of Permendagri No. 20 of 2018. The purpose of this study is to analyze the suitability of Village Financial Reporting and Accountability conducted by Dawuan Kaler Vilage Subang Regency with the 2022 budget year, in the process of analyzing this suitability will be compared between Reporting and Accountability Village Finance in Dawuan Kaler Village Subang Regency with Permendagri No. 20 of 2018 concerning village financial management. The data that has been collected is analyzed and presented with a qualitative descriptive research method. The results of the study showed that the village head office of Dawuan Kaler at the village APB Reporting stage didn’t comply with Permendagri No. 20 of 2018 while at the village APB Accountability stage, the Dawuan Kaler Village Head Office is in accordance with Permendagri No. 20 of 2018.